Lead wetting of thin nickel films deposited onto GaAs - Gladkikh, N.T.; Dukarov, S.V. (STC “Institute for Single Crystals”, 1996)
The wetting of nickel films deposited onto (111) face of GaAs single crystals with island lead condensates has been studied. The wetting angle, θ, is found to depend on the Ni film thickness, t, and to change within the limits defined by wetting of pure GaAs (t = 0, θ ≈ 120°) and compact-state nickel wetting (t > 20 nm, θ ≈ 20°). The change of θ is explained as due to the surface heterogeneity arising as a result of chemical interaction between nickel film and gallium arsenide and of nickel dissolution in the liquid lead. - - - - - - - - - - - - - - - - Изучено смачивание островковыми конденсатами свинца пленок никеля, нанесенных на монокристалл арсенида галлия (грань (111)). Установлено, что краевой угол θ зависит от толщины t пленки Ni и изменяется в крайних пределах, соответствующих смачиванию чистого GaAs (t = 0, θ ≈ 120°) и смачиванию никеля в компактном состоянии (t > 20 nm, θ ≈ 20°). Изменение θ объясняется гетерогенностью смачиваемой поверхности, возникающей в результате химического взаимодействия пленки никеля с арсенидом галлия и растворения никеля в жидком свинце.
Keywords: Thin films; Wetting; Research Subject Categories::NATURAL SCIENCES::Physics::Condensed matter physics::Surfaces and interfaces